(untitled) (Web of Teachers: Inderscience Research, 2025)
This scientific article deeply analyzes the specific role and importance of philosophical worldview in the formation of human thinking and consciousness. Philosophical worldview is considered not only a means of understanding existence, but also an important spiritual basis that determines the moral, aesthetic and social position of a person. The article consistently highlights the factors of formation of this worldview, its differences from other - religious, scientific and mythological - worldviews, as well as the stages of historical development.